Maternal Characteristics of Women Exposed to Hypnotic Benzodiazepine Receptor Agonist during Pregnancy - Bjarke Askaa; Espen Jimenez-Solem; Henrik Enghusen Poulsen; Jon Traerup Andersen (Obstetrics and Gynecology International)
Background. There is little knowledge regarding the characteristics of women treated with hypnotic benzodiazepine receptor agonists (HBRAs) during pregnancy. In this large Danish cohort study, we characterize women exposed to HBRA during pregnancy. We determined changes in prevalence of HBRA use from 1997 to 2010 and exposure to HBRAs in relation to pregnancy. Methods. We performed a retrospective cohort study including 911,017 pregnant women in the period from 1997 to 2010. Information was retrieved from The Danish Birth Registry and The Registry of Medicinal Product Statistics to identify pregnant women redeeming a prescription of HBRAs. Results. We identified 2,552 women exposed to HBRAs during pregnancy, increasing from 0.18% in 1997 to 0.23% in 2010. Compared to unexposed women, exposed women were characterized by being older, with higher BMI, in their third or fourth parity, of lower income and education level, more frequently smokers, and more likely to be comedicated with antipsychotic, anxiolytic, or antidepressant drugs (P<0.0001). Conclusion. Women using HBRAs during their pregnancy differ from unexposed women in socioeconomic factors and were more likely to receive comedication. The consumption of HBRAs was reduced during pregnancy compared to before conception.